2020
DOI: 10.3390/foods9111645
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Spoilage Microbiota and Cyclopiazonic Acid Mycotoxin with Chestnut Extract Enriched Chitosan Packaging: Stability of Inoculated Gouda Cheese

Abstract: Active chitosan-based films, blended with fibrous chestnut (Castanea sativa Mill.) tannin-rich extract were used to pack Gouda cheese that has been contaminated with spoilage microflora Pseudomonas fluorescens, Escherichia coli, and fungi Penicillium commune. A comprehensive experimental plan including active chitosan-based films with (i) chestnut extract (CE), (ii) tannic acid (TA), and (iii) without additives was applied to evaluate the film′s effect on induced microbiological spoilage reduction and chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
(82 reference statements)
1
8
0
Order By: Relevance
“…This could be related to the chemical composition of the extract, as chestnut extract may have a higher fiber content (prone to clumping from certain concentrations) than JKRB and, certainly, to the different extraction procedures, which implies variability in the particle sizes of the dry extract powder. Other studies [ 35 , 56 ] affirm uniform preparation on a lab scale, thus supporting previous statements. It was impossible to pinpoint exactly how the authors of the Ref.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…This could be related to the chemical composition of the extract, as chestnut extract may have a higher fiber content (prone to clumping from certain concentrations) than JKRB and, certainly, to the different extraction procedures, which implies variability in the particle sizes of the dry extract powder. Other studies [ 35 , 56 ] affirm uniform preparation on a lab scale, thus supporting previous statements. It was impossible to pinpoint exactly how the authors of the Ref.…”
Section: Resultssupporting
confidence: 84%
“…In comparison to neat polylactic acid foils, a biofoil is considered to have good performance when its tensile strength varies between 24.8 and 70.2 MPa [ 62 ], depending on the application (more for food packages and less for medical scaffolds). Relative to the chitosan (blank) biofoil, the JKRB biofoil with incorporated extract in a concentration of 0.01 mg mL −1 (1%) did not display outstanding performance with regard to tensile strength, only increasing it by up to 1.81 MPa, which was much lower than that achieved using chestnut extract (0.01 mg mL −1 , 15.6 MPa) [ 35 ] or curcumin extract (0.08 mg mL −1 , 18.8 MPa) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many studies have shown that the incorporation of cellulose nanomaterials as an additive could improve the performance of the food packaging films [ 20 , 21 , 22 ]. Further advances in nanocellulose research in biopolymers film are quite promising for active packaging applications, including the controlled release packaging and responsive packaging [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%